CD4+ and CD8+ T-cell kinetics in aviremic HIV-infected patients developing Hodgkin or non-Hodgkin lymphoma. (13th March 2016) - Hoffmann, Christian; Schommers, Philipp; Wolf, Eva; Müller, Markus; Schultze, Alexander; Krznaric, Ivanka; Stoehr, Albrecht; Wolf, Timo; Fäktenheuer, Gerd; Stier, Bastian; Wyen, Christoph; Hentrich, Marcus
Abstract : Objective: The risk of non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL) is increased in HIV-infected individuals. We studied the kinetics of lymphocyte subsets in patients who subsequently developed HL or NHL while on virologically suppressive antiretroviral therapy (ART). Design: Using a nested case–control design, cases of HIV+ HL or NHL were selected from two prospective clinical studies. Aviremia was defined as less than 200 HIV-RNA copies/ml for at least 6 months prior to lymphoma diagnosis. Each case was matched to three aviremic HIV+ controls without lymphoma. Results: In the 81 cases (50 HL and 31 NHL), prediagnostic CD4 + T cells and CD8 + T cells displayed discordant kinetics compared with controls. Within the last and within the next-to-last year preceding HL diagnosis, mean CD4 + T cells decreased by −168 and by −2 cells/μl, compared with an increase of +44 and +73 cells/μl in the controls, respectively. Mean CD8 + T cells decreased by −352 and −115 cells/μl, compared with nonsignificant changes of −29 and ±0 cells/μl in the controls, respectively. T-cell kinetics demonstrated a marked inter-individual variability. Kinetics of CD4 + and CD8 + T cells were also discordant between NHL cases and controls. Conclusion: This study on a large number of aviremic patients developing HL and NHL who were carefully matched with controls, gives insights to prediagnostic kinetics of immune parameters. The discordant kinetics of both CD4 + and CD8 + T cells are already seen 1–2 years prior to lymphoma diagnosis, are more pronounced during the last year and in patients developing HL but are also seen in NHL.